Bones never lie [compact disc, unabridged] : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2014)
"Unexpectedly called in to the Charlotte PD's Cold Case Unit, Dr. Temperance Brennan wonders why she's been asked to meet with a homicide cop who's a long way from his own jurisdiction. The shocking answer: Two child murders, separated by thousands of miles, have one thing in common--the killer. Years ago, Anique Pomerleau kidnapped and murdered a string of girls in Canada, then narrowly eluded capture. It was a devastating defeat for her pursuers, Brennan and police detective Andrew Ryan. Now, as if summoned from their nightmares, Pomerleau has resurfaced in the United States, linked to victims in Vermont and North Carolina. When another child is snatched, the reign of terror promises to continue--unless Brennan can rise to the challenge and make good on her second chance to stop a psychopath. But Brennan will have to draw her bitter ex-partner out of exile, keep the local police and feds from one another's throats, and face more than just her own demons as she stalks the deadliest of predators into the darkest depths of madness" --